People first! Intellectual capital and growth of high-growth social cooperatives (social gazelles) in the startup stage. Evidence from Italy - Cattafi, Giulia; Del Pozzo, Antonio; Nicolò, Domenico (Piccola Impresa / Small Business, 2023)
Purpose. This paper aims to investigate the relationship between Intellectual Capital (IC) and the revenues in high-growth social cooperatives in the startup phase (social gazelles). Design/methodology/approach. Using the OECD definition, we have selected all 85 social cooperatives born in Italy in 2014that became gazelles in 2018 or 2019. Applying the VAIC model, we measured the IC of these companies. Then we performed a panel regression analysis with fixed-effects specification to test our hypotheses regarding the effect exerted by the efficiency of human capital, structural capital and capital employed on the revenues of social gazelles. Findings. The empirical analysis revealed that both Human Capital Efficiency (HCE) and Capital Employed Efficiency (CEE) have a positive effect on revenues of the Italian social gazelles. On the other side, we found a negative relationship between Structural Capital Efficiency (SCE) and the revenues of these companies. Practical and Social implications. From a theoretical point of view, this paper contributes to the literature on high-growth firms (HGFs) shedding light on a topic still little explored. It also highlighted possible future lines of research. From a practical point of view, examining the relationship between IC and revenues of social gazelles, this study provides useful insights to design social startups. Originality of the study. This paper fills a gap in the literature by highlighting the positive role of human capital efficiency (HCE) and capital employed efficiency (CEE) in the revenue of social gazelles.